Investigating expectancy norms of English-Chinese translation of children’s literature in China - Dongmei, Men; Malini Ganapathy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The past decades have seen a growing trend both in the quantity and quality of the translation of children’s literature (TCL). There have been a growing number of publications focusing on TCL. However, few studies have investigated TCL from the perspective of norm theory, and prior research has primarily concentrated on the implied reader while ignoring actual readers. This study aimed to investigate the expectancy norms of real readers of English-Chinese(E C) TCL, Chinese children (12 and below) and adult readers (19 and above) and determine whether there are any differences between them. A list of 17 items was obtained according to the results of the semi-structured interviews and questionnaires conducted by Bijani et al. (2014) and Khoshsaligheh et al. (2020). An online questionnaire was conducted among 679 participants to gain insights into their attitudes towards E-C TCL. Key findings show that the highest-rated expectancy norms of children and adults differ, as does the priority of the top six expected features, suggesting that children and adults have diverse expectancy norm preferences. The top 3 highest ranked features of current Chinese children’s readers are clarification of the ambiguous content, the plot of translations, and immersing themselves in the story, while the top 3 most important features for current Chinese adult readers are plot of translations, vivid illustrations, immersing themselves in the story. Children readers tend to place a greater emphasis on the educational values of the translated text, while adult readers prioritise enjoying their reading experience. These findings have implications for stakeholders such as publishers, translators, and educators who are involved in the production and dissemination of translated children’s literature in China.